Visions and revisions in Sanskrit narrative: studies in the Sanskrit epics and Purāṇas - Balkaran, Raj; Taylor, McComas (Asian studies series monograph, 2023)
Introduction: Visions and revisions of Sanskrit narrative -- 1. Narrative argument and interlocutory frames in the Mahābhārata / Greg Bailey -- 2. Āstīka, black magic and apotropaic ritual: Peacemaking brahmins and the snake sacrifice in the Mahābhārata’s Adiparvan / Adam Bowles -- 3. Transitions and transmissions in the Mahābhārata: Revisiting the Ugraśravas/Śaunaka frame dialogue / Brian Black -- 4. Battling inner conflicts: Dhṛtarāṣṭra and Saṃjaya in the Udyogaparvan of the Mahābhārata / Angelika Malinar -- 5. The Ambopākhyāna reconsidered: Reading Ambā’s story as part of the Rāma Jāmadagnya myth cycle / Brian Collins -- 6. Claiming the narrative: subjectivity and intertextuality in the Ambopākhyāna / Zuzana Špicová -- 7. Bhīma: The shadow king / Sudha Berry -- 8. Some moral tasting notes on the Udyogaparvan of the Mahābhārata / James M. Hegarty -- 9. The Bhagavadgītā’s determinism and world literature / Simon Brodbeck -- 10. Mineral, vegetal, animal or divine? The flying palace Puṣpaka’s manifold metamorphoses / Danielle Feller -- 11. From Ayodhyā to the Daṇḍaka: Rāma’s journey in exile according to the Jain Rāmāyaṇas / Eva De Clercq -- 12. Gembedded narratives: Jewelled peacetime tales of Rāma’s exile and Rāvaṇa’s domicile as alternative afterlife anticipations in the Vālmīki Rāmāyaṇa / Shubha Pathak -- 13. Train stations, enterprising priests and the deadly blows of kuśa grass: Reading the purāṇas with a magic‑realist lens / Laurie L. Patton -- 14. Textures of purāṇic transmission: A contemporary vernacular exposition of a Sanskrit purāṇa / Sucharita Adluri -- 15. The Śivaśarmopākhyāna of the Padma Purāṇa as a bizarre compendium of epic and purāṇic tales of Pitṛbhakti / Nicolas Dejenne -- 16. Same, same but different: The Tamil Kāñcippurāṇam and its Sanskrit source / Jonas Buchholz -- 17. The ‘purāṇification’ of the death of Kṛṣṇa / Christopher R. Austin -- 18. Lambs, lightning, nakedness and fire: Polythetic networks and literary elaborations of the Purūravas–Urvaśī narrative / McComas Taylor.